2023
DOI: 10.1136/military-2022-002285
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical performance during British Army Junior Entry, British Army Standard Entry and Royal Air Force Basic Training

Abstract: IntroductionThe purpose was to quantify physical performance in men and women during British Army Junior Entry (Army-JE), British Army Standard Entry (Army-SE) and Royal Air Force (RAF) basic training (BT).DesignProspective longitudinal study.Methods381 participants ((339 men and 42 women) n=141 Army-JE, n=132 Army-SE, n=108 RAF) completed a 2 km run, medicine ball throw (MBT) and isometric mid-thigh pull (MTP), pre-BT and post-BT. To examine changes in pre-BT to post-BT physical test performance, for each cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Although older than typical British Army recruits, our participants were of a relatively similar fitness level. Our participants performed the 2‐km run slower than has been reported for British Army recruits (Rue et al, 2023), but demonstrated similar aerobic capacity as measured by VO 2peak . The study cohort as a whole demonstrated a pre‐training VO 2peak of 45.3 ± 8.0 ml·kg −1 ·min −1 , whereas British Army recruits reported an VO 2max of 44.8 ± 4.9 ml·kg −1 ·min −1 (Williams, 2005).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although older than typical British Army recruits, our participants were of a relatively similar fitness level. Our participants performed the 2‐km run slower than has been reported for British Army recruits (Rue et al, 2023), but demonstrated similar aerobic capacity as measured by VO 2peak . The study cohort as a whole demonstrated a pre‐training VO 2peak of 45.3 ± 8.0 ml·kg −1 ·min −1 , whereas British Army recruits reported an VO 2max of 44.8 ± 4.9 ml·kg −1 ·min −1 (Williams, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…The study cohort as a whole demonstrated a pre‐training VO 2peak of 45.3 ± 8.0 ml·kg −1 ·min −1 , whereas British Army recruits reported an VO 2max of 44.8 ± 4.9 ml·kg −1 ·min −1 (Williams, 2005). For the seated medicine ball throw, British Army recruits reported an average distance of 4.33 ± 0.83 m (Rue et al, 2023). Study participants demonstrated an average throw distance of 3.64 ± 0.97, however the study group was ∼46% women, whereas the military group was only ∼16% women.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in findings between those studies and the current study is unknown. Historically, strength adaptations may be deemed suboptimal after 14 weeks of British Army BT ( 47 , 48 ) with recruits typically making only small improvements in muscular strength (men = 7 ± 11% and women = 0 ± 10%) ( 48 ). More recently, mid-thigh pull force did not change (−0.7 ± 20.6%, p = 0.144) in 132 British Army recruits after 14 weeks of BT ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, strength adaptations may be deemed suboptimal after 14 weeks of British Army BT ( 47 , 48 ) with recruits typically making only small improvements in muscular strength (men = 7 ± 11% and women = 0 ± 10%) ( 48 ). More recently, mid-thigh pull force did not change (−0.7 ± 20.6%, p = 0.144) in 132 British Army recruits after 14 weeks of BT ( 47 ). Internationally, suboptimal strength adaptations have been reported during military training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation